2017
DOI: 10.1103/physreva.96.053407
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved Wigner time delay in atomic photoionization: The 4d subshell of free and confined Xe

Abstract: The angular dependence of photoemission time delay for the inner nd 3/2 and nd 5/2 subshells of free and confined Xe is studied in the dipole relativistic random phase approximation. A finite spherical annular well potential is used to model the confinement due to fullerene C60 cage. Nearcancellations in various of the dipole amplitudes, Cooper-like minima, are found. The effects of confinement on the angular dependence, primarily confinement resonances, are demonstrated and detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
(81 reference statements)
1
28
0
Order By: Relevance
“…Although the agreement in the threshold region is not as good, the main features of the experiment are reproduced. Our theoretical calculations are in excellent agreement with the predictions of Mandal and coworkers 35 , 36 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…Although the agreement in the threshold region is not as good, the main features of the experiment are reproduced. Our theoretical calculations are in excellent agreement with the predictions of Mandal and coworkers 35 , 36 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…The nd correlation with inner core is only noticeable near corresponding deeper thresholds. We can also easily incorporate the effect of a fullerene cage [36] to model a RABBITT process in encapsulated atoms. Eventually, we will attempt to generalize our model to account for inter-shell correlation.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant theoretical work on the angle-dependent time delay, for example, Refs. [26][27][28][29][30][31][32], but fewer related experimental reports [12,28,33], all using the RABBITT technique. The Wigner delay is theoretically isotropic for single-photon ionization of He, but Heuser et al [28] observed an angular dependence in photoemission delay, attributed to the XUV þ IR two-photon ionization process, inherent in RABBITT interferometry.…”
Section: Introductionmentioning
confidence: 99%